Iron ore : mineralogy, processing and environmental sustainability - Lu, Liming (Woodhead Publishing is an imprint of Elsevier, 2015)
Iron Ore: Mineralogy, Processing and Environmental Issues summarizes recent, key research on the characterization of iron ores, including important topics such as beneficiation (separation and refining), agglomeration (e.g., production of pellets or powders), blast furnace technology for smelting, and environmental issues relating to its production. The text is an ideal reference on the topic during a time when iron ore production has increased significantly, driven by increasing demand from countries such as India and China.
Keywords: Iron ores.; Iron mines and mining -- Environmental aspects.; elektronické knihy; electronic books